The salt god's daughter (Catapult, Soft Skull Press, 2012)
“Beautifully evokes scenes of two girls adrift in the . . . bohemian beach culture . . . a breathtaking, fiercely feminine take on American magical realism.” —Interview Magazine Set in Long Beach, California, beginning in the 1970s, The Salt God’s Daughter follows Ruthie and her older sister Dolly as they struggle for survival in a place governed by an enchanted ocean and exotic folklore. Guided by a mother ruled by magical, elaborately-told stories of the full moons, which she draws from The Old Farmer’s Almanac, the two girls are often homeless, often on their own, fiercely protective of each other, and unaware of how far they have drifted from traditional society as they carve a real life from their imagined stories. Imbued with a traditional Scottish folktale and hints of Jewish mysticism, The Salt God’s Daughter examines the tremulous bonds between sisters and the enduring power of maternal love—a magical tale that presents three generations of extraordinary women who fight to transcend a world that is often hostile to those who are different. “Indeed, Ruby has written a complicated, multi-layered work that shifts shapes to bridge the relationship between tragedy and redemption.” --The Huffington Post “Three generations of indelibly original women wrestle with the confines of their lives against a shimmering backdrop of magic, folklore, and deep-buried secrets . . . To say I loved this book is an understatement.” --Caroline Leavitt, New York Times bestselling author “The selkie myth lies at the heart of Ruby’s second novel . . . This is a bewitching tale of lives entangled in lushly layered fables of the moon and sea.” --Kirkus Reviews

Hockey (Checkerboard how-to library, ,, 1996)
Explains how to play hockey, briefly discussing equipment, skating basics, team positions, and game techniques.

Predicting ground-water vulnerability to nitrate in the Puget Sound Basin (Fact sheet), FS 97-061,, 1997)
Description Not Provided